ANALISIS PENGARUH BERAT BADAN LEBIH TERHADAP PENURUNAN FUNGSI MEMORI JANGKA PENDEK PADAANAK UMUR 8 – 12 TAHUN DI SD CAHAYA NUR KABUPATEN KUDUS - Sri Hartini; Biyanti Dwi Winarsih (Universitas Muhammadiyah Semarang, 2014)
The prevalence of obesity in children has increased in the last three decades. Obesity inchildren has high risk to be adults’ obesity, and potentially suffers metabolic disease anddegenerative diseases in the future. The emergence of the problem of decline in cognitivefunction in childrens to be another important consequence of the explosion of obesity-relatedhealth problems. Memory function is one of the cognitive functions in which the speed ofcognitive processes known to depend on the degree of activation of short-term memory. Thepurpose of this study was to determine the relations between body weight over with thereduction of short-term memory fuction in childrens at age 8-12 year olds.The study involved 65 body weight over respondents aged 8-12 year olds in the CahayaNur Elementary School Kudus. This study was quantitative research using correlational analyticmethod with retrospective approach.This study obtained the rate of respondents’ Body Mass Index at the precentil 94,39. Theresults of the average value of short-term memory function in the obese childrens was lower(14.53) compared with the average value of overweight childrens (16.26). The results of bodyweight over and short-term memory fuctions analysis using the regresi logistic generating ρvalue 0.001 or < level of significance (α: 0.05) with a correlation coefficient (r) -0.386.The conclustion of this study is there was a significant relations with negative correlationand the strength of a weak correlation between body weight over with the reduction of the shorttermmemoryfuctioninchildrensaged8-12yearolds.Keywords : Body Weight Over, Short-Term Memory Function.